Dynamics of Resource Governance, Resource Scarcity and Conflict in Nepal - Upreti, Bishnu (Journal of Forest and Livelihood, 2004)
This paper discusses the relationships between governance practices in natural resources and conflict in Nepal. Within the governance framework, the paper examines the roles of laws, policies, and practices increating or minimizing scarcity and conflict and their impacts on society and resource management. The paper argues that resource conflicts produce both positive and negative consequences and alter existing social relations. This paper concludes that the existing approaches, strategies and discourses have not been able to address new challenges and, therefore, need a fresh paradigm.